2003
DOI: 10.1002/eat.10168
|View full text |Cite
|
Sign up to set email alerts
|

The role of palatable food and hunger as trigger factors in an animal model of stress induced binge eating

Abstract: These effects suggest that binge eating in this model is motivated by reward, not metabolic need, and parallels observations of binge triggers described in clinical binge-eating disorders. This strengthens the validity of using this animal model to target the physiology and treatment of eating disorders preceded by dieting and stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
139
1
3

Year Published

2003
2003
2007
2007

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 185 publications
(157 citation statements)
references
References 63 publications
14
139
1
3
Order By: Relevance
“…These findings extend the recent observations of Hagan et al (2002Hagan et al ( , 2003, Dallman and co-workers (Pecoraro et al, 2004), and the earlier reports of Morley et al (1983) on the role of stress in palatable food-taking behavior. We also found that hungry rats that are given intermittent access to palatable food during training escalate their lever responding during nonreinforced timeout periods, suggesting the development of compulsive food-taking behavior and (or) increases in the motivational impact of the food-associated cues.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These findings extend the recent observations of Hagan et al (2002Hagan et al ( , 2003, Dallman and co-workers (Pecoraro et al, 2004), and the earlier reports of Morley et al (1983) on the role of stress in palatable food-taking behavior. We also found that hungry rats that are given intermittent access to palatable food during training escalate their lever responding during nonreinforced timeout periods, suggesting the development of compulsive food-taking behavior and (or) increases in the motivational impact of the food-associated cues.…”
Section: Discussionsupporting
confidence: 91%
“…To our knowledge, this is the first demonstration of progressive escalation of food-taking behavior in an operant model. Our data extend results from nonoperant studies in which food-restricted rats given intermittent access to palatable food progressively increased their food intake, an effect interpreted to indicate the development of binge-eating habits (Colantuoni et al, 2001;Hagan et al, 2002Hagan et al, , 2003Corwin and Buda-Levin, 2004). …”
Section: Progressive Increase In Food-taking Behavior During Trainingsupporting
confidence: 84%
See 2 more Smart Citations
“…Current binge eating models emphasize a role for dietary restraint in promoting binge behavior (Howard and Porzelius, 1999), with many animal models positing that a history of quantitative food restriction, modeled by limiting the daily caloric ration (eg 66% of daily intake) (Hagan et al, 2003) or the duration of daily food access (eg 2 h) (Inoue et al, 2004), is central to bingeing. However, an alternative conceptualization might emphasize the qualitative aspect of dietary restraint, namely the attempted abstinence of binge eaters from 'forbidden,' palatable foods (Kales, 1990;Knight and Boland, 1989;Fletcher et al, 2007;Mitchell and Brunstrom, 2005;Gonzalez and Vitousek, 2004;Stirling and Yeomans 2004;Corwin, 2006;Corwin and Buda-Levin, 2004).…”
Section: Introductionmentioning
confidence: 99%